2009
DOI: 10.1016/j.devcel.2008.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The Jekyll and Hyde Functions of Caspases

Abstract: Apoptosis is an ancient form of regulated cell death that functions under pathological and non-pathological contexts in all metazoans. More than a decade of intense research has led to extensive characterization of the core molecular mechanisms for apoptotic cell death. This includes the identification of a family of cysteine proteases, caspases, which are critical for the execution of apoptosis. Whereas completion of the proteolytic caspase cascade leads to elimination of a cell by apoptosis, caspase activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
127
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 123 publications
1
127
0
1
Order By: Relevance
“…In addition to the various mechanisms that regulate caspases during apoptosis, many studies have shown that active caspases play important roles in nonapoptotic cellular functions, including inflammation, protein secretion, and differentiation (reviewed in Kuranaga and Miura 2007;Li and Yuan 2008;Feinstein-Rotkopf and Arama 2009;Yi and Yuan 2009). Caspase activity in the absence of a cell death signal may have unintended deadly consequences in the absence of finely tuned regulation.…”
Section: Caspase Regulation In Nonapoptotic Cellular Processesmentioning
confidence: 99%
“…In addition to the various mechanisms that regulate caspases during apoptosis, many studies have shown that active caspases play important roles in nonapoptotic cellular functions, including inflammation, protein secretion, and differentiation (reviewed in Kuranaga and Miura 2007;Li and Yuan 2008;Feinstein-Rotkopf and Arama 2009;Yi and Yuan 2009). Caspase activity in the absence of a cell death signal may have unintended deadly consequences in the absence of finely tuned regulation.…”
Section: Caspase Regulation In Nonapoptotic Cellular Processesmentioning
confidence: 99%
“…We focused on caspase 3, the major apoptotic effector enzyme that acts in conjunction with initiator caspases 8 and 9, which are involved in alternate apoptotic pathways and in some cases cell activation. 31 To quantify caspase activity, we used a fluorescently conjugated caspase-specific substrate that can be combined with cell-surface staining to compare apoptotic activity between the GC and This suggests that reduced apoptosis may be contributing to the phenotypic differences observed between WT and AID Ϫ/Ϫ GCs. Because antibiotic treatment revealed an immunization-dependent increase in the GC compartment of AID Ϫ/Ϫ mice, we tested caspase activity in these mice as well.…”
Section: Reduced Apoptosis In Aid ؊/؊ Gc B Cellsmentioning
confidence: 99%
“…We focused on caspase 3, the major apoptotic effector enzyme that acts in conjunction with initiator caspases 8 and 9, which are involved in alternate apoptotic pathways and in some cases cell activation. 31 To quantify caspase activity, we used a fluorescently conjugated caspase-specific substrate that can be combined with cell-surface staining to compare apoptotic activity between the GC and For personal use only. on March 28, 2019. by guest www.bloodjournal.org From follicular (ie, background) populations.…”
mentioning
confidence: 99%
“…Antiapoptotic control relies on antiapoptotic proteins activation (Bcl 2, Bcl XL) and IAPs (c-IAP-1, SURVIVIN, LIVIN, XIAP, etc.) (4,10). There are certain proteins in the cell that inhibit initiator caspases, but IAPs are the only known endogenous proteins that regulate the activity of both initiator and effector caspases (11).…”
Section: Function and Inhibition Of Caspasesmentioning
confidence: 99%